Aby Warburg and Classical Reception Studies in Spain: History of a Discipline - Martín-Esperanza, Paloma (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
In recent decades a new discipline has been consolidated in Spain which, within the framework of art-historical studies, has received the name of Classical reception studies (Antikenrezeption). Its origins can be traced back to the German school and, specifically, to the thinking of Aby Warburg (1866- 1929) and his disciples, who coined and perfected the methodology proposed by their master for the study of the survival of antiquity in other historical periods (das Nachleben der Antike). The late arrival of Warburg’s proposals in Spain has not, however, prevented the development of a discipline which, having emerged mainly as an evolution of the Historiography of Ancient History and Archaeology, has in recent years been linked to German reception theory and Warburg’s methodological approach, resulting in an interdisciplinary discussion that should be framed within cultural history research. This paper studies the influence of Warburg’s and his Warburg-Kreis thought in the Spanish academic world and its relationship with the development and consolidation of the Classical reception studies.
Keywords: Spain; Warburg; reception; legacy; Antiquity; historiography